Psychiatric drugs dispensing trends in the affected population following Brumadinho dam failure - Marcelo Farah Dell'Aringa; Gabriel Elias Correa-Oliveira; Francesco Della Corte; Luca Ragazzoni; Ives Hubloue; Virginia Murray; Thais Piazza; Claudia Garcia Serpa Osorio-de-Castro; Elaine Miranda; Francesco Barone-Adesi (Frontiers in Public Health)
IntroductionIn January 2019 D1 tailing Dam Failed in Brumadinho, Minas Gerais, Brazil. Two hundred and seventy people were immediately killed when 11.7 million cubic meters of mining byproducts were released, promoting major destruction and environmental damage traveling through the Paraopeba river basin. This study aims to investigate the impact of this disaster in the dispensing of psychiatric drugs.MethodsWe evaluated monthly aggregated data from 12 months before to 12 months after the event from two data sources, one accounting for psychiatric drugs dispensed by private pharmacies and the other by public health services. We compared the median dispensing of benzodiazepines and antidepressants from the periods before and after the event using the Mann Whitney test and performed a visual analysis of line graphs from both datasets.ResultsData shows an increase of 294% in dispensing of benzodiazepines in the month following the event with a return almost to the baseline subsequently. When comparing the periods before and after the event the increase was not statistically significant, going from 16.03 to 20.60 daily defined daily doses (DDD) per 1,000 inhabitants (p = 0.07). In the private sector dispensing increased from 8.54 to 11.70 (p = 0.01), whereas in the public it went from 6.67 to 8.91 (p = 0.15). Data on the dispensing of antidepressants showed a statistically significant increase in the period following the event, going from 44.15 daily DDD per 1,000 inhabitants to 53.32 (p = 0.02). In the public sector it rose from 27.89 to 32.43 (p = 0.20), and in the private from 14.90 to 22.03 (p < 0.01).DiscussionWe observed a peak in the dispensing of benzodiazepines in the month following the event drawn by the dispensing of diazepam in the public health sector. Dispensing of both benzodiazepines and antidepressants tended to be higher in the period following the event. Our findings should be taken carefully due to the nature of the data used for the study. This study can serve as a call for more evidence and local guidelines on acute psychiatric pharmacological care following disasters and for better integration of pharmaceutical assistance in disaster plans.